(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
The system is offered non-destructive radiothermal and radar methods of control of technological parameters of heat-resistant wares from sitall, sitall and quartz ceramics in the workplace. The mechanism of removal and treatment of information is developed about the controlled parameters of dielectric wares, allowing to provide necessary authenticity of control.